The invasive snail Melanoides tuberculata in Argentina and Paraguay - Peso, Juana Guadalupe (2011)
This article reviews the spread and current distribution of the invasive snail Melanoides tuberculata in Argentina and Paraguay based on data from specimens deposited in museums, published reports and field collections. Field collections were made between April 1999 and May 2010. Snails were searched for using different collecting methods in a variety of habitats. Specimens were identified according to a categorical scoring system based on shell traits and anatomy was compared with published descriptions. Only five records for Argentina and none for Paraguay were found in published reports. The first report of M. tuberculata in Argentina was in 1999. Neither specimens from Argentina nor Paraguay were found in the Argentine Museum of Natural Sciences (MACN). In La Plata Museum (MLP) the only material from these countries was that associated with the published reports. During the course of surveys undertaken since 1999, M. tuberculata was recorded at 19 sampling locations. The presence of this species in Paraguay is reported here for the first time. Since its discovery in Argentina and Paraguay, the snail has colonized both lotic and lentic habitats with a variety of substrata. The records suggest that the species is established and that its introduction resulted from passive dispersal. Actually, spreading is believed to occur by active dispersal (i.e. active migration) from established populations and impact in native communities is expected.